Venous thromboembolism prophylaxis in major orthopaedic surgery: A multicenter, prospective, observational study - Altintas, Faik; Gurbuz, Hakan; Erdemli, Buelent; Atilla, Buelent; Ustaoglu, Recep Guer; Ozic, Ugur; Kinik, Hakan (Turkish Assoc Orthopaedics Traumatology, 2008)
Objectives: We investigated risk factors for venous thromboembolism (VTE), prophylaxis measures employed, and incidence of symptomatic deep venous thrombosis (DVT) and pulmonary embolism (PE) in patients undergoing major orthopaedic surgery (MOS). Methods: An open, multicenter, prospective, observational study was conducted in 21 medical centers, comprising 899 patients. Of these. 316 patients (35.2%) underwent total hip arthroplasty (THA), 328 patients (36.5%) underwent total knee arthroplasty (TKA), and 255 patients (28.4%) underwent surgery for hip fractures (HF). Pharmacologic prophylaxis was employed in all the patients. Results: Risk factors for VTE were seen in 73.2% of the patents. the most common being obesity (72%) and prolonged immobilization (36.3%). Low-molecular-weight heparin (91.1%) and fondaparinux (8.9%) were used for prophylaxis, which was short-term in 273 patients (30.4%) and long-term in 626 patients (69.6%). Mechanical prophylaxis was performed with compression stockings in 610 patients (67.9%) and by intermittent pneumatic compression in 67 patients (7.5%). During three-months of follow-up, symptomatic DVT and PE were seen in eight (0.9%) and four patients (0.4%), respectively. Mortality occurred in 10 patients (1.1%). Complications of major and minor bleeding were seen in eight (0.9%) and 40 (4.5%) patients, respectively. Conclusion: Effective VTE prophylaxis is associated with low risk of clinically apparent DVT and PE in MOS.
Majör ortopedik cerrahilerde venöz tromboemboli profilaksisi: Çokmerkezli, prospektif, gözlem çalışması
Keywords: Anticoagulants/therapeutic use; arthroplasty, replacement, hip; arthroplasty, replacement, knee; postoperative complications; risk factors; thromboembolism; venous thrombosis